Critical Investigation of the Worldview in Islam: Inspiration from the Thought of Syech Muhammad Naquib Al-Attas - Putri, Dini Aulia Apriansyah; Handayani, Feby Lia; Munbaits, Tika Bilqis; Julyani, Tri Nadia; Amrillah, Rizki (EDUCTUM: Journal Research, 2024)
The purpose of this article is to delve into the depth and relevance of the thought of Sheikh Muhammad Naquib Al-Attas in facing the challenges of the dominant modern worldview. Through comprehensive analysis, this article aims to highlight how his thinking influences the conceptualization of the Islamic worldview, both by offering new frameworks and strengthening traditional concepts. The research method used is literature study with a qualitative approach, gathering and analyzing various relevant literature sources, including the direct works of Sheikh Muhammad Naquib Al-Attas and writings discussing his thoughts. The research findings indicate that Al-Attas's thinking highlights the challenges faced by the Muslim community in confronting the Western secular worldview embedded in modern science. Al-Attas emphasizes the importance of referring to the heritage of Islamic scholars' thinking in kalam, philosophy, and Sufism in Islamic history, as well as reformulating it according to the current context. The concept of Islamization of knowledge and Islamic education oriented towards shaping complete individuals becomes a crucial foundation in building resilient and characterful generations. However, the challenge of integrating modern science and Islamic values, as well as the risk of losing the integrity of traditional values, needs to be wisely addressed in efforts to acculturate Al-Attas's thought into the discourse of the global worldview.